Fungicide resistant Trichoderma strains causing compost infection in shiitake production - Turóczi, Gy.; Kovácsné Gyenes, M.; Vajna, L.; Balázs, S. (International Journal of Horticultural Science, 2002)
Trichoderma infection represents the major problem of shiitake production in the growing house of the Research Institute at Kecskemet. Heavy infections occur mainly on the compost before spawn run. All the isolated strain belongs to the species Trichoderma harzianurn, but morphology of the colony indicates that there are more strains liable for the infection. Source of infection remained unclear but the Trichoderma strains can be considered as weed moulds rather than true pathogens of shiitake. All the Trichoderma isolates showed unusual high degree of resistance to fungicides.